2020
DOI: 10.25035/ijare.13.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Who are the Older Adults Who Drown in Western Australia? A Cluster Analysis Using Coronial Drowning Data

Abstract: Drowning amongst older people is a growing concern. Exploring demographic and other factors associated with unintentional drowning incidents amongst older adults may assist to identify key target groups and refine prevention strategies. This study sought to examine the heterogeneity of older individuals who have drowned and identify population subgroups in Western Australia (WA). A cluster analysis was used to segment the population by examining coronial data 2001-2018 (n = 93). Analysis identified four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Population projections indicated that hundreds of older adults could fatally drown each year in Australia and Canada by the year 2050. However, the epidemiology and risk factors associated with drowning among older adults have received scant attention in the literature, prevention strategies even less so (Abercromby et al, 2020;Peden et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population projections indicated that hundreds of older adults could fatally drown each year in Australia and Canada by the year 2050. However, the epidemiology and risk factors associated with drowning among older adults have received scant attention in the literature, prevention strategies even less so (Abercromby et al, 2020;Peden et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(Gillespie et al, 2012). Partnering with the healthy ageing and falls prevention sectors could increase the impact of older adult drowning prevention efforts (Abercromby et al, 2020). Medical conditions were present among the majority of older adults who died from drowning; heart disease in particular was frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young people (particularly males aged over 16 years) in HICs are at greater risk of drowning, attributed to risk-taking behaviours, peer pressure, poor aquatic competency and alcohol use [ 8 , 21 , 24 , 25 ]. In contrast, for older adults (65 years and over) in HICs, risks relate to bathing, falls into water, poor health, alcohol consumption, medication use and lack of safety preparation around natural water bodies or during recreational activities [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%